2022
DOI: 10.1177/01614681221105008
|View full text |Cite
|
Sign up to set email alerts
|

Mothers and Children Doing Mathematics Together: Implications for Teacher Learning

Abstract: Background/Context: There is much to understand about how parents and children interact around mathematics, particularly with families whose home language is different from the children’s main language of schooling. Families of immigrant origin are likely to bring experiences and knowledge that may be different from what their children’s schools expect or value. Educators can benefit greatly from a better understanding of these experiences and the nature of the parent–child mathematical interactions. Purpose/F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…To illustrate, equity scholars in mathematics education have issued calls to reconsider what counts as mathematics and the types of math valued in formal education settings, as these forms are rooted in histories of discrimination and marginalization (Aguirre et al, 2017; Civil, 2016; Gutiérrez, 2018). Although research has identified the rich ways children engage in math in their homes and communities, such as while engaging in household chores or assisting in family businesses (Booker & Goldman, 2016; Civil & Andrade, 2002; Civil & Quintos, 2022; Civil et al, 2008), these experiences are undervalued, or even blamed, for contributing to students' misconceptions (Aguirre et al, 2017; Civil, 2016). Indeed, Civil and Andrade (2002) documented that students who were most successful in math were those who adapted readily to school math practices rather than those who used their home‐based experiential knowledge as a springboard.…”
Section: Problematizing What We Mean By Equity In Stemmentioning
confidence: 99%
“…To illustrate, equity scholars in mathematics education have issued calls to reconsider what counts as mathematics and the types of math valued in formal education settings, as these forms are rooted in histories of discrimination and marginalization (Aguirre et al, 2017; Civil, 2016; Gutiérrez, 2018). Although research has identified the rich ways children engage in math in their homes and communities, such as while engaging in household chores or assisting in family businesses (Booker & Goldman, 2016; Civil & Andrade, 2002; Civil & Quintos, 2022; Civil et al, 2008), these experiences are undervalued, or even blamed, for contributing to students' misconceptions (Aguirre et al, 2017; Civil, 2016). Indeed, Civil and Andrade (2002) documented that students who were most successful in math were those who adapted readily to school math practices rather than those who used their home‐based experiential knowledge as a springboard.…”
Section: Problematizing What We Mean By Equity In Stemmentioning
confidence: 99%
“…The two studies on Latine caregiver‐child math language showed that language matters, but only one intentionally addressed linguistic variations. We need work that moves beyond translating available schemes (developed for monolingual English speakers) to explore language‐based variations in family math, including how bilingual families use both languages in math‐related experiences (see Civil & Quintos, 2022, for examples of translanguaging —the fluid use of two languages in parents' math interactions with older children).…”
Section: Moving Toward a Sociocultural Understanding Of Family Mathmentioning
confidence: 99%
“…While research on family math with culturally and linguistically nondominant U.S. families of school‐aged children has been done (e.g., Booker & Goldman, 2016; Civil et al., 2008; Civil & Andrade, 2002; Civil & Quintos, 2022), scant attention has been paid to racial, ethnocultural, or linguistic diversity in such research with families of children under age 5. Indeed, in a recent review of family math studies, only 29% of descriptive studies—key in generating foundational knowledge—included racially/ethnically diverse families (others studied predominantly White samples or did not report ethnicity; Eason et al., 2022).…”
mentioning
confidence: 99%
“…These studies used questionnaires and interviews to obtain information from parents and teachers about parental involvement and its impact. The second category involves interventions related to the parent (Civil, 1998;Civil & Quintos, 2002;Civil, Diez-Palomar, Menendez & Acosta-Iriqui, 2008;Eisenreich & Andreasen, 2016;Jay, Rose & Simmons, 2017;Mangram & Metz, 2018;Morkoyunlu & Konyalıoğlu, 2020;Xiao, Namukasa & Zhang, 2016). The researcher's experiences as a teacher were influential in conducting this study.…”
Section: Introductionmentioning
confidence: 99%